Motivadores e inibidores que influenciam na adesão dos jovens aos planos de previdência complementar patrocinados - Pereira, Rodrigo Sisnandes (2020)
Brazilian Social Security System is facing rearrangements concerning the rising of minimum age of retirement, and reduction of payments impacting especially young people. Meanwhile, private pension is gaining relevance due to people’s needs of having their own retirement savings. Although some companies offer their employees patronized plans where there is a contribution of the same amount of money, lots of workers do not adhere to the plan. Therefore, this research aims to analyze motivators and inhibitors influencing the adhesion of young people to the complementary patronized pension plan. In order to achieve its goals, this exploratory and qualitative study reviewed literature that helped creating a set of motivating and inhibiting factors for the adhesion. Later on, it was conducted 35 interviews with young employees of public and private companies who participate or not in the patronized pension plans. Results confirmed the factors from other studies. It was also identified a factor not presented in the literature as an inhibitor, the distrust. Based on this data, it was presented a set of inhibitors and motivators for the adhesion and also defined four profiles of young workers: (1) Public young prevented; (2) Young private prevented; (3) Young public unprepared; and (4) Young private unprepared. Lastly, it was proposed a set of recommendations to stimulate the adhesion of complementary pension plans. These recommendations can stimulate the adhesion to plans and the building of savings for retirement.